Investigating Insecticide Resistance Mechanisms In Dengue Vectors Population; Aedes Aegypti And Aedes Albopictus In Penang Island - Jalaluddin, Nur Iwani (2019)
In Malaysia, the vector of arboviral diseases especially Aedes aegypti and Ae. albopictus has long been known as a vector that could transmit dengue viruses. Currently, chemical control is considered as the most efficient way to control the dengue vectors in the dengue outbreak areas. However, the heavy reliance on chemical control has resulted in the development of insecticide resistance in the dengue vectors due to the presence of insecticide resistance mechanism. This study highlights the susceptibility status of both dengue vectors exposed to permethrin and malathion insecticides via WHO adult mosquito bioassay test. The mechanisms involved in the insecticide resistance of dengue vectors by focusing on target-site resistance mechanism via genotyping the voltage gated sodium channel gene (VGSC), and Acetylcholinesterase gene (Ace-1) have been identified via polymerase-chain reaction (PCR) assays. The presence of metabolic resistance mechanisms has been investigated through biochemical enzyme assays and quantitative PCR (qPCR) in the samples of dengue vectors collected from Sungai Ara (SA), Jelutong (JG) and Balik Pulau (BP) areas of Penang Island. The insecticide susceptibility study showed that the adult Ae. aegypti samples from SA, JG and BP were resistant towards permethrin 0.25% and 0.75%, while the Ae. aegypti from all three sampling areas were susceptible towards malathion 5%.